Pig and dairy pathways out of poverty in India - International Livestock Research Institute (International Livestock Research Institute, 2008)
This film illustrates how small-scale pig keeping and dairying have the potential to help hundreds of thousands of the poorest people in Assam and Nagaland, remote provinces in northeast India, to increase their incomes and better their lives.